Determinan Minat Masyarakat Kabupaten Belitung dalam Menyalurkan Wakaf - Wulpiah Wulpiah; Hidayati Ida (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2026)
This study aims to analyze the Interest of the People of Belitung Regency in Distributing Money Waqf which is measured by the factors of Socialization, Religiosity and Income both partially and simultaneously. with a sample of 100 respondents. Furthermore, the data collection technique used is a printed questionnaire distributed to 100 respondents as a primary data source. The type of research is Associative which is carried out to explain the relationship between two or more variables. The results of the study show that if the Religiosity variable partially affects the Interest in Distributing Money Waqf with a value of tcalcal>ttable or 4,170>1,290, it means that H1 is accepted and H0 is rejected. The Socialization variable partially affects the Interest in Disbursing Money Waqf with a tcal>ttable value or 2,492<1,290 meaning that H2 is accepted and H0 is rejected. Meanwhile, the Income variable partially affects the Interest in Disbursing Money Waqf with a tcal>ttable value or 1,291>1,290 meaning that H3 is accepted and H0 is rejected. Simultaneously, the variables of religiosity, socialization and income have an effect on the Interest in Distributing Waqf Money with a value of 22,581 while the Ftable is obtained from the formula df=-k-1 or 100-3-1= 96, which is 2.14. where Fcal>Ftabel or 22,581>2.14 means that H4 is accepted, H0 is rejected.